The Relationship Between Noun Phrase And Verb Phrase - Japen Sarage (Universitas Ahmad Dahlan, 2014)
AbstractAmong words classes or parts of speech a noun and a verb or precisely a noun phrase and a verb phrase play a very important role in syntax. In English, they mark the presence of sentence. The relationship between them is very close that one may cause the presence of another. This is often called a subject-predicate relationship and their degree is a bilateral dependency i.e. the verb phrase determines the noun phrase called valence and the noun phrase determines the verb through agreement (Bussman, 1996:1139). Other relationships among different phrases are one-sided or in the form of modifiers, subordinators, or complementizers, one is more important than others.This paper attempts to discuss a noun phrase and a verb phrase as the main part of a sentence. Some special characteristics of the noun phrase and the verb phrase are discussed. This paper also tries to see if other sentence elements such as an adjectival, adverbial, and prepositional phrases can have an emphasis in a sentence.